KONSEP NAMIMAH DALAM KITAB AL-AZKAR IMAM NAWAWI SEBAGAI UPAYA MENCEGAH HOAKS DI ERA DIGITAL - Gasmi, Nur Muhammad; Susilawati, Reni; Ainul Gani; Guntur Cahaya Kesuma; Amirudin (LPPM STAI Muhammadiyah Probolinggo, 2025)
In the digital era, the spread of hoaxes has become a significant concern, leading to social instability, misinformation, and erosion of trust. This study aims to explore the concept of Namimah in Imam Nawawi's Al-Azkar Book as a means to prevent hoaxes. Namimah, or the spread of false information, is considered a serious sin in Islamic teachings. The rapid development of digital technology has facilitated the spread of information, including hoaxes, at an unprecedented rate. This has resulted in the proliferation of misinformation, which can have serious consequences. In this context, it is important to review Islamic teachings that can provide guidance on how to address this issue. This study aims to analyze the concept of Namimah in Imam Nawawi's Al-Azkar Book and its relevance in preventing hoaxes in the digital era. This study uses a literature study approach, where Imam Nawawi's Al-Azkar Book is analyzed to identify and interpret the concept of Namimah. The analysis was conducted through qualitative content analysis methods. This study reveals that Namimah is considered a serious sin in Islamic teachings, and Imam Nawawi emphasizes the importance of verifying information before spreading it. The concept of Namimah is also closely related to other Islamic values, such as honesty, trustworthiness, and justice. This study concludes that the concept of Namimah in Imam Nawawi's Al-Azkar Book provides valuable insights to prevent hoaxes in the digital era. By understanding the importance of verifying information and the consequences of spreading false information, individuals can play an important role in preventing the spread of hoaxes. This study highlights the relevance of Islamic teachings in dealing with contemporary issues and provides a framework for promoting a culture of truth and integrity in the digital era.